EFFECT OF USING AN ANDROID-BASED MODULE ON KNOWLEDGE AND ATTITUDE OF NURSING STUDENTS ABOUT THE PROVISION OF TRANSCULTURAL NURSING - Apriani Susmita Sari; Elsi Dwi Hapsari; Widyawati Widyawati (Belitung Nursing Journal, 2020)
Background: The essence of transcultural nursing is to guide nursing students in order to be able to provide nursing care based on patients’ needs and their cultural backgrounds. To transfer the knowledge and attitude of the transcultural nursing effectively among generation Z students, an android-based module can be used and it is considered effective. Objective: This study aimed to determine the effect of using an android-based module on the knowledge and attitudes of nursing students regarding the provision of transcultural nursing. Methods: This study employed a quasi-experiment with a non-equivalent control group design. Ninety-four students were selected using a purposive sampling, which forty-seven were assigned in an android-based module group and a printed-module group. Data were measured using knowledge and attitude questionnaires about transcultural nursing, and perceived usefulness and perceived ease of use questionnaire for android-based modules. Data were analyzed using paired t-test and independent t-test with a significance level of < .05. Results: There was a significant effect of both android and printed based modules on knowledge of transcultural nursing (p <.05), but not for the attitude (p >.05). Based on the Independent t-test, there was no significant difference in students' knowledge and attitude about transcultural nursing between both groups (p >.05). However, the android-based module was considered useful (97.9%) with a mean value of 44, and was easy to use (91.5%) with a median value of 40. Conclusion: The use of both printed-based module and android-based module is effective to increase the students’ knowledge and attitudes about transcultural nursing.